Influence of 3D Barriers on Walkability for the Elderly in a German City - Hartmut Müller; Konstantin Geist; Klaus Böhm; Markus Schaffert (Tehnički Glasnik)
Walking is a sustainable, safe, and active mode of transportation. The benefits that the elderly in particular gain from outdoor walking are manifold, be it free and independent access to stores and services of all kinds or the opportunity to socialize, enjoy parks, et cetera. This article depicts one particular factor that affects outdoor walkability, namely the gradient of walking paths. Steep slopes can be a serious obstacle to walkability, primarily for older people. The evaluation of available geospatial data sources formed the basis for a geospatial analysis of walkability in the larger city of Kaiserslautern, located in southwest Germany. The concept of Walk Score was used to quantify the results obtained. The results demonstrate that the Walk Score can be refined to better address the mobility needs of older adults. The methodology was implemented for the German city of Kaiserslautern by integrating volunteered geographic information with high-quality official datasets.